EASIX-guided risk stratification for complications and outcome after CAR T-cell therapy with ide-cel in relapsed/refractory multiple myeloma - Xiang Zhou; Patrick Costello; Anita Schmitt; Carsten Müller-Tidow; Peter Dreger; Michael Schmitt; Max Topp; Hartmut Goldschmidt; Hermann Einsele; Nikhil C Munshi; Marc S Raab; Joseph Kauer; et al. (Journal for ImmunoTherapy of Cancer)
Background Chimeric antigen receptor (CAR) T-cell therapy has demonstrated significant benefits in the treatment of relapsed/refractory multiple myeloma (RRMM). However, these outcomes can be compromised by severe complications, including cytokine release syndrome, immune effector cell-associated neurotoxicity syndrome (ICANS) and immune effector cell-associated hematotoxicity (ICAHT), predisposing for life-threatening infections.Methods This retrospective observational study examined a total of 129 patients with RRMM who had received idecabtagene vicleucel (ide-cel) at two major myeloma centers in Germany and one center in the USA to assess the Endothelial Activation and Stress Index (EASIX) as a risk marker for an unfavorable clinical course and outcome after CAR T-cell therapy. EASIX is calculated by lactate dehydrogenase (U/L) × creatinine (mg/dL) / platelets (109 cells/L) and was determined before lymphodepletion (baseline) and at the day of CAR T-cell infusion (day 0). The analysis was extended to EASIX derivatives and the CAR-HEMATOTOX score.Results An elevated baseline EASIX (>median) was identified as a risk marker for severe late ICAHT, manifesting with an impaired hematopoietic reconstitution and pronounced cytopenias during the late post-CAR-T period. Patients with high EASIX levels (>upper quartile) were particularly at risk, as evidenced by an increased rate of an aplastic phenotype of neutrophil recovery, severe late-onset infections and ICANS. Finally, we found associations between baseline EASIX and an inferior progression-free and overall survival. Moreover, the EASIX at day 0 also demonstrated potential to serve as a risk marker for post-CAR-T complications and adverse outcomes.Conclusions In conclusion, EASIX aids in risk stratification at clinically relevant time points prior to CAR T-cell therapy with ide-cel. Increased EASIX levels might help clinicians to identify vulnerable patients to adapt peri-CAR-T management at an early stage.